WOMEN'S REPRESENTATION AND PARTICIPATION IN THE STRATEGIC DECISION-MAKING STRUCTURE OF THE MERAH PUTIH COOPERATIVE IN SOUTH BUTON - La Didi; Rasmuin; Nafiruddin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study analyzes women's representation and participation in the strategic decision-making structure of the Merah Putih Cooperative in South Buton Regency. Using a descriptive quantitative approach through the Gender Representation Index (IRG), this study found that women's representation in the management structure is still low, namely 4% in the core management, 1% in the chair position, and 0% in the supervisory position, with a total structural representation of 10% of the 560 members. In terms of participation, women's presence in the formation of the cooperative reached 20%, but active participation in discussions (4%), program proposals (2%), and budget determination (3%) indicated limited involvement. Furthermore, no women utilized access to cooperative financing (0%). These findings indicate a gap between formal representation and women's substantive influence in the decision-making process. This study confirms that increasing the number of women in the organizational structure does not automatically result in an equal distribution of power. More inclusive and gender-responsive cooperative governance reforms are needed to achieve meaningful and sustainable participation.